Analisis Perbandingan Kualitas Pelayanan Jasa Ekspedisi KALOG, Herona Express, dan LNP di Stasiun Purwokerto - Iswanto, Ary Putra; Puspitasari, Mariana Diah; Imron, Nanda Ahda; Nopriyanto, Windi; Kurniawan, Safrudin; Anisha, Artika Dewi Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The volume of BHP courier transportation in Indonesia in 2021 increased by 265% from 2017. The purpose of this study was to determine the difference in the quality of services provided to users of BHP courier transportation services between KALOG, Herona Express, and LNP expedition services at Purwokerto Station. The sample used in this study are 100 respondents with purposive sampling technique sampling. The attributes used as a reference are the five dimensions of service quality, which were Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This study used a descriptive analysis method, Service Performance (SERVPERF), and MANOVA. The results of this study showed from overall service quality dimensions score. With the highest total average score (4,123) obtained by KALOG expedition services, then Herona Express (4.118), and the lowest total average score (4.056) obtained by LNP expedition services. From the results of the MANOVA comparison test, it is known that the tangible dimension is the dimension with the most significant difference in the comparison between: KALOG expedition services with Herona Express, KALOG expedition services with LNP, and Herona Express expedition services with LNP.